2018
DOI: 10.5194/bg-15-4205-2018
|View full text |Cite
|
Sign up to set email alerts
|

Community composition and seasonal changes of archaea in coarse and fine air particulate matter

Abstract: Abstract. Archaea are ubiquitous in terrestrial and marine environments and play an important role in biogeochemical cycles. Although air acts as the primary medium for their dispersal among different habitats, their diversity and abundance is not well characterized. The main reason for this lack of insight is that archaea are difficult to culture, seem to be low in number in the atmosphere, and have so far been difficult to detect even with molecular genetic approaches. However, to better understand the trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Although the miniLEO system overall does not appear to be conducive for either of these environments (low pH and anaerobic conditions), the gradual increase in Thermoplasmata (from 2.6% in the surficial sample to 11.9% in Depth_70 samples) is suggestive of pockets of microenvironments for such metabolisms to thrive and/or likelihood of organisms with novel metabolic strategies. Additionally, the absence of Euryarcheota in the parent material and irrigation water suggests that air is most likely the source, as highlighted in a recent study (Wehking et al, ), which shows Euryarcheota as a dominant airborne archaea in the fine particulate matter. Overall, our study revealed a highly diverse bacterial population and comparatively less diverse archaeal population in the incipient terrestrial basalt soil system subjected to enhanced weathering processes.…”
Section: Discussionmentioning
confidence: 91%
“…Although the miniLEO system overall does not appear to be conducive for either of these environments (low pH and anaerobic conditions), the gradual increase in Thermoplasmata (from 2.6% in the surficial sample to 11.9% in Depth_70 samples) is suggestive of pockets of microenvironments for such metabolisms to thrive and/or likelihood of organisms with novel metabolic strategies. Additionally, the absence of Euryarcheota in the parent material and irrigation water suggests that air is most likely the source, as highlighted in a recent study (Wehking et al, ), which shows Euryarcheota as a dominant airborne archaea in the fine particulate matter. Overall, our study revealed a highly diverse bacterial population and comparatively less diverse archaeal population in the incipient terrestrial basalt soil system subjected to enhanced weathering processes.…”
Section: Discussionmentioning
confidence: 91%
“…At the phylum level, the archaea Crenarchaeota was sharply lower (<1%) in the phyllosphere but higher in both air and soil samples, which concurred with the previous study ( Vorholt, 2012 ). The shared of Crenarchaeota within air, phyllosphere, and soil suggested that soil may be a possible source of archaea affecting adjacent air ( Wehking et al, 2018 ). Previous studies have found that the bacterial families of Rhizobiaceae and Pseudomonadaceae are commonly observed in plants, which would help create differences in composition of the phyllosphere, air, and soil samples ( Yanni et al, 1997 ; Hunter et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…19,64,68 Variations over seasons and in airmass origin were also linked to changes in aerosol microbial community composition. 1,2,6,9,69,70 The aerobiome community composition displays mixtures of sources, and detecting a constant and stable indigenous microbial community was not yet reported. As such, the identi ed microorganisms may serve as tracers for the sources contributing to the aerobiome.…”
Section: Discussionmentioning
confidence: 99%